Correction: Research and application of digital measure management and control technology for characteristic low-efficiency gas wells in Gas Field A. - Hao-Yang Li; Wen-Hai Ma; Jun-Liang Li; Pin-Gang Ma; De-Song Yao; Ming-Xi Feng; Shao-Xing Gu (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0323644.].